2021
DOI: 10.3961/jpmph.21.071
|View full text |Cite
|
Sign up to set email alerts
|

Did the Timing of State Mandated Lockdown Affect the Spread of COVID-19 Infection? A County-level Ecological Study in the United States

Abstract: Previous pandemics have demonstrated that several demographic, geographic, and socioeconomic factors may play a role in increased infection risk. During this current coronavirus disease 2019 (COVID-19) pandemic, our aim was to examine the association of timing of lockdown at the county level and aforementioned risk factors with daily case rate (DCR) in the United States. Methods:A cross-sectional study using publicly available data was performed including Americans with COVID-19 infection as of May 24, 2020. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Thus, the lockdown policy was suboptimal. The timing of the lockdown orders was significantly associated with the spread of COVID-19 after adjusting for various socio-demographic, geographic, and health-related factors [ 33 ]. Over time, many policies have been issued by the government to prevent the spread.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lockdown policy was suboptimal. The timing of the lockdown orders was significantly associated with the spread of COVID-19 after adjusting for various socio-demographic, geographic, and health-related factors [ 33 ]. Over time, many policies have been issued by the government to prevent the spread.…”
Section: Discussionmentioning
confidence: 99%
“…Culminating in the rise of self-reported stress levels and depressive symptoms [10]. What’s interesting to take into account is how many countries were implementing swift lockdown measures to mitigate the spread of COVID-19 [14]. In contrast, the United States of America (USA) opted for individual states to choose their lockdown policies.…”
Section: Introductionmentioning
confidence: 99%
“…This made it difficult for individuals to determine what sources were correct and what information applied to the specific lockdown restriction they were in depending on their state. Timing of when a state enacted a mask mandate had a significant association with the spread of COVID-19 [14]. Recent research has suggested that state-level policy differences may be associated with different outcomes concerning the COVID-19 pandemic [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, the federal government at this time opted for a hands-off approach to COVID-19 and allowed individual states to decide on the best ways to limit the spread of this deadly disease [1]. This variation in leadership led to differing outcomes in terms of the spread of COVID-19 [26]. These mandates to protect the public ranged from school and work closures to stay-at-home orders, all of which can have important effects on several aspects of an individual’s life.…”
Section: Introductionmentioning
confidence: 99%